Key indicators of strategic management and foresight in a company - Céspedes Revelo, Róger Wilfredo (2018)
The main objective research was to determine that the key indicators of management have a significant impact on the Strategic Foresight of the Scotiabank Huánuco branch during 2016; to establish the incidents, the profitability, adaptability and productivity were taken into account as dimensions of the independent variable, as well as the strategic vision, market of financial services and finance strategy, as dimensions of the dependent variable, materialized in 14 indicators with data collected through the survey administered to 64 clients of the Bank with experience in the financial service; was applied a applied research, of descriptive type, with a correlational dimension, of explanatory level, characterizing its problematic; transactional, for being descriptive-explanatory and correlational; the study population is represented by the subsidiaries of the banking companies located in the district of Huánuco; the sample is represented by the Scotiabank Huánuco branch, chosen for its business size and volume of operations; the research methods employed are observation, analytical, descriptive-explanatory, inductive, deductive and synthetic; The techniques and instruments used for the collection of data are the documentary analysis-bibliographic record; the survey - questionnaire; for data processing; inferential descriptive statistics was used to present the results. The results obtained correspond to each problem, the objectives and the hypothesis, since it is observed that there are averages of estimates that exceed 3.5 points (4.40), which correspond to the indicators from 1 to 14, considering themselves as favorable and real in the research process, reaching the conclusion that 80% of the average respondents consider the Scotiabank Huánuco branch as simple, flexible, reliable, strong, solid, safe, profitable, efficient, effective, adaptable, innovative, and sustainable that guarantees them credibility and confidence.